Knowledge, Attitude, and Practices Related to COVID-19 Among Individuals with Mental Illness: A Cross-sectional Study - Aparna Goyal, Shipra Singh, Purushottam Jangid, Sidharth Arya, Abhishek Kumar, Jagriti Yadav, Isha Batra (RUHS Journal of Health Sciences)
Introduction: Novel COVID-19 virus was declared a pandemic and brought unprecedented changes globally. People with mental illness were expected to be at higher risk because of their increased vulnerability to get infected due to decreased sensitivity to threats, cognitive impairment, lack of becoming a source of infection along with limited awareness and intent to access health resources. Adequate knowledge, positive attitude, and good practices lead to an effective intervention in battling this pandemic and their levels need to be assessed to ascertain their safety from this global catastrophe. Methodology: A cross-sectional study was conducted on 405 patients aged between 18 to 60 years with global assessment of functioning (GAF) score >50 presenting to a tertiary care centre in Haryana. A specially designed proforma to collect socio-demographic and clinical details along with knowledge, attitude, and practices (KAP) related to COVID-19 was used to collect data. Results: A total of 385 patients were analysed and mean scores of knowledge, attitude, and practices were found to be 11.05±2.39, 5.64±1.54, and 5.98±1.54, respectively indicating fair know-ledge, positive attitude, and good practices among our target population. Better education, employment, and urban locality were associated with better KAP among our patients, Conclusion: A significant positive correlation among know-ledge, attitude, and practice was observed regarding COVID-19 individual with mental illness. Further research is needed where population based and epidemiological prospective comparative control studies should be conducted.